2004
DOI: 10.1289/ehp.5955
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of personal polycyclic aromatic hydrocarbon exposures among pregnant minority women in New York City.

Abstract: As part of a multiyear birth-cohort study examining the roles of pre-and postnatal environmental exposures on developmental deficits and asthma among children, we measured personal exposures to polycyclic aromatic hydrocarbons (PAHs) among 348 pregnant women in northern Manhattan and the South Bronx, New York. Nonsmoking African-American or Dominican women were identified and recruited into the study. During the third trimester of pregnancy, each subject wore a personal air monitor for 48 hr to determine expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
94
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 25 publications
4
94
0
Order By: Relevance
“…Although Krakow has relatively high ambient concentrations of PAHs from coalburning, levels are within the range seen in other urban areas worldwide. [56][57][58][59] Mechanisms by which stressors such as material hardship, PAHs, or their combination exert effects on the developing brain are not well understood. However, laboratory studies have identified changes in N-methyl-Daspartate receptor expression, reduced brain-derived neurotrophic factor mRNA, 6 and epigenetic changes 60,61 in response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although Krakow has relatively high ambient concentrations of PAHs from coalburning, levels are within the range seen in other urban areas worldwide. [56][57][58][59] Mechanisms by which stressors such as material hardship, PAHs, or their combination exert effects on the developing brain are not well understood. However, laboratory studies have identified changes in N-methyl-Daspartate receptor expression, reduced brain-derived neurotrophic factor mRNA, 6 and epigenetic changes 60,61 in response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the predictors of personal PAH exposures was performed by Tonne et al [7]. In that study the personal exposure of 344 women from NYC ranged from 0.06 ng/m 3 for dibenz [a,h]anthracene (DahA) to 4.1 ng/m 3 for pyrene.…”
Section: Introductionmentioning
confidence: 99%
“…The published data evaluated the PAH exposure among pregnant women mostly based on personal air monitoring or PAH-DNA adduct levels. Detailed analysis of environmental exposure to PAH derived from US and Polish cohorts of pregnant women shows that personal PAH exposure was 10-fold higher in Kraków than in New York City (NYC) (average: 39.1 ng/m The studies have indicated that diesel fuel combustion contributes to ambient PAH in NYC, whereas coal burning in small furnaces is a major source of PAH in Kraków [7,8].The analysis of the predictors of personal PAH exposures was performed by Tonne et al [7]. In that study the personal exposure of 344 women from NYC ranged from 0.06 ng/m 3 for dibenz [a,h]anthracene (DahA) to 4.1 ng/m 3 for pyrene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Personal air monitoring of women in New York City found that pyrene had the highest mean concentration among the PAHs measured (22). Personal air monitoring for PAHs is difficult and expensive and does not capture exposure from dietary sources, making development of a good biological exposure marker highly desirable.…”
Section: Introductionmentioning
confidence: 99%